Health and Environment (Journal of Bangladesh Academy of Sciences, 2022)
Bangladesh is passing through the dividend phase of demographic transition, with 45 million (over a quarter of the total population) in the age group of 15-29 years and 52.8 million (about a third) in the 15-36 age group. Young scientists belong to the upper segments of the later age group (some may be somewhat older than 36), who will in the fullness of time, take up leadership positions in their respective fields. Whatever be the field of human endeavour, the capability of the protagonists, is certainly a pivotal key to success. Indeed, human capability depends on education, skill training and health services. The better the availability of these services, the better is expected to be the ability acquired by the people concerned. One of these key services, health, is included in the theme of this conference. This paper has proposed that a universal health coverage (UHC) system be developed in Bangladesh so that people from all walks of life can access at least primary health services. The UHC can be developed centering around the 14,000 or so Community Clinics in place all around rural Bangladesh. Bangladesh is pursuing the goal of sustainable development within the UN adopted 2030 Agenda for Sustainable Development framework. This agenda is anchored on three pillars-economic, social and environmental. Sustainable development can be succinctly defined as socially acceptable, environmentally sound economic growth. Also, a basic tenet characterising sustainable development is that nobody can be left behind, i.e., everybody has to be included. The theme of this conference consist of the environmental pillar of sustainable development. In fact, the environment is the ultimate resource base of all development. Climate change, a major sub-set of environmental issues, is fast deteriorating and becoming an existential threat to humanity. This paper has discussed what has been happening in relation to climate change and what is being done to combat the menace globally and in Bangladesh. The efforts of Bangladesh in policy, programming, funding, and action in the context of responding to the increasingly adverse impacts on the country caused by the worsening climate change have been reviewed. Also, since this problem is global and cannot be adequately combatted by any one country, much less by a resource-poor country like Bangladesh, what role the international community is playing in this regard has been examined. The final section relates the lessons from the above discussions and reviews the future roles that young scientists need to play. J. Bangladesh Acad. Sci. 46(2); 129-134: December 2022